Cement-based bridge deck maintenance and rescue material and preparation method thereof
By adjusting the proportion of key components in cement-based bridge deck maintenance and rescue materials, the problems of long repair cycles and poor adhesion of existing materials are solved, and efficient repair of materials and improved driving safety are achieved.
Patent Information
- Application Number
- CN202311686528.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-12-11
AI Technical Summary
The repair cycle of existing cement-based bridge deck maintenance and rescue materials is relatively long, and the repair time cannot be controlled. Moreover, the adhesion between the materials and the original bridge deck paving layer after repair is not strong, the impact resistance and low compressive strength are poor, which affects driving safety.
A cement-based bridge deck curing and rescue material is used, and the formula includes calcium sulfoaluminate cement, gypsum, silicate cement, silica fume, quartz sand, fiber, redispersible latex powder, dyes, boric acid, carbonate and polycarboxylic acid high-performance water reducing agent, etc., to adjust the proportion of these materials to regulate the settling time and mechanical properties of the materials.
The adhesion and impact resistance of the repaired materials and the original bridge deck paving layer are improved, and the adjustable effect of repair construction time is achieved, the traffic closure time is shortened, and driving safety is improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road surface repair materials, and in particular to a cement-based bridge deck maintenance and rescue material and a preparation method thereof. Background Art
[0002] Bridge expansion joints, bridge-roadbed junctions, large interchanges, toll booth entrances and exits, and other regional transition sections, due to large changes in road stiffness and long-term exposure to the atmosphere, the use environment is relatively harsh. Under the frequent impact force, the pavement layer of the road and bridge is prone to early damage due to stress concentration, mainly manifested in concrete and steel bond failure, concrete cracking, new and old concrete bond failure, etc. These road and bridge pavement defects not only reduce the driving comfort of drivers and passengers, but more importantly, affect the appearance of the road and bridge deck and normal transportation capacity, shortening the service life of transportation facilities.
[0003] However, the conventional cement maintenance and rescue materials currently used in repairing road and bridge pavement layers have a long maintenance cycle, require long-term traffic closures, affect road traffic efficiency, and the repair time cannot be adjusted; in addition, the conventional maintenance and rescue materials have weak adhesion to the original bridge pavement layer, poor impact resistance, and low compressive strength. They are prone to poor adhesion after repair and are easily broken after impact, affecting driving safety. Summary of the invention
[0004] The present invention provides a cement-based bridge deck maintenance and rescue material and a preparation method thereof, which are used to solve the problems that the current maintenance cycle of the road bridge deck pavement layer is long and the repair time cannot be adjusted; the maintenance and rescue material after repair has weak adhesion to the original bridge deck pavement layer, poor impact resistance, low compressive strength, and affects driving safety.
[0005] The invention provides a cement-based bridge deck maintenance and rescue material. The maintenance and rescue material comprises the following raw materials in proportion by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.1 parts of expansion agent and 0.01-0.05 parts of graphene.
[0006] Optionally, the maintenance and rescue materials include the following raw materials in the following weight proportions: 25-30 parts of calcium sulfoaluminate binder, 5-10 parts of gypsum, 2-4 parts of Portland cement, 1-5 parts of silica fume, 54-57 parts of quartz sand, 0.5-1 parts of fiber, 1.5-2 parts of redispersible latex powder, 0.4-0.6 parts of colorant, 0.1-1 parts of boric acid, 0.05-0.5 parts of carbonate, 0.5-1 parts of polycarboxylic acid high-performance water reducer, 0.1-0.5 parts of hydroxypropyl methylcellulose, 0.2-0.3 parts of surfactant, 0.1-0.2 parts of resin, 0.05-0.06 parts of expansion agent, and 0.02-0.03 parts of graphene.
[0007] Optionally, the strength grade of the calcium sulfoaluminate binder is 72.5, and the strength grade of the silicate cement is 42.5.
[0008] Optionally, the quartz sand comprises, by weight: 35-45 parts of quartz sand with a particle size of 10-20 mesh, 7-15 parts of quartz sand with a particle size of 40-70 mesh, and 8-15 parts of quartz sand with a particle size of 70-140 mesh.
[0009] Optionally, the fibers are mixed with polyacrylonitrile fibers and nano-carbon fibers in a mass ratio of (1-2):1.
[0010] Optionally, the expansion agent is a mixture of a calcium oxide expansion agent and a magnesium oxide expansion agent in a mass ratio of (1-1.5):1.
[0011] Optionally, the carbonate is lithium carbonate or sodium carbonate, and the resin is a water-absorbing resin.
[0012] Optionally, the mass ratio of carbonate to graphene is 6:(0.5-5).
[0013] Optionally, the mass ratio of the resin to the expansion agent is 1:(0.05-1.2).
[0014] The present invention also provides a method for preparing a cement-based bridge deck maintenance and rescue material. The preparation steps of the maintenance and rescue material are as follows:
[0015] Weigh the following raw materials by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.08 parts of expansion agent, and 0.01-0.05 parts of graphene;
[0016] Calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed uniformly in a dry powder state to obtain dry material A;
[0017] The expansion agent and the resin are mixed evenly in a dry powder state to obtain dry material B;
[0018] Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, and 4wt%-6wt% of water is added thereto and stirred to mix evenly to obtain slurry C;
[0019] Mix dry material A, slurry C, and 70% of a surfactant, add 6wt%-8wt% of water thereto, and stir and mix well to obtain slurry D;
[0020] Mix the dry material B, slurry D and dye, add 1wt%-3wt% of water into them, stir and mix evenly into the curing rescue material.
[0021] The cement-based bridge deck maintenance and rescue material provided by the present invention improves the adhesion and impact resistance of the repaired maintenance and rescue material to the original bridge deck pavement layer through the mutual synergistic effect of multiple components, and realizes the adjustable effect of the construction time of the maintenance and rescue material. The setting time of the maintenance and rescue material is mainly regulated by adjusting the ratio between the five elements of calcium sulfoaluminate binder, gypsum, silicate cement, carbonate and boric acid in the material to meet the different needs of customers. The traffic closure duration can be regulated within an arbitrary range of 1-6 hours according to the needs, thereby minimizing the impact of the closed construction on traffic.
[0022] Multiple levels of quartz sand with different particle sizes are configured, with large-particle quartz sand as the main component and small-particle quartz sand as the auxiliary component, so that the small-particle quartz sand can fill more gaps between the large-particle quartz sand, thereby improving the strength and hardness of the maintenance and rescue materials.
[0023] A special proportion of polyacrylonitrile fiber and nano-carbon fiber is added to the maintenance and rescue material. Nano-carbon fiber has the characteristics of high aspect ratio and high toughness, and plays the bridging role of fiber, penetrating the pores inside the maintenance and rescue material, making the internal connection of the maintenance and rescue material tighter, thereby enhancing the bridging role of polyacrylonitrile fiber, further improving the tightness of the material inside, thereby effectively resisting the intrusion of external media and enhancing the durability of the maintenance and rescue material.
[0024] By using a special ratio of carbonates and graphene, graphene can be filled in the grid structure of the maintenance and rescue material, so that the hydration product gel and the material are more densely combined. The carbonate converts the Ca(OH)2 gel into CaCO3, which can fill the pores and gaps in the hardened cement body, optimize the microstructure of the hardened cement body, and increase the density. The synergistic effect of the two can improve the early strength, corrosion resistance and frost resistance of the cement. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present invention.
[0026] The invention provides a cement-based bridge deck maintenance and rescue material. The maintenance and rescue material comprises the following raw materials in proportion by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.1 parts of expansion agent and 0.01-0.05 parts of graphene.
[0027] The early strength of the maintenance and rescue materials is mainly provided by calcium sulfoaluminate binder, gypsum and silicate cement. Among them, calcium sulfoaluminate binder has high durability, chemical corrosion resistance and good strength development characteristics, and has a short hardening time, which can improve construction efficiency. Portland cement also has the characteristics of short hardening time and high early strength. Gypsum can delay the setting time of the material. In the hydration reaction, gypsum can react with tricalcium aluminate in the material to form calcium sulfonate, forming a cement protective film to prevent the cement from reacting too quickly. Carbonate can improve the early strength of cement and shorten the initial setting time and final setting time of the material. At the same time, boric acid is added to the maintenance and rescue materials. Boric acid can be used as a retarder to delay the initial setting time and final setting time of the material without destroying the early and late strength of the maintenance and rescue materials. The setting time of the maintenance and rescue materials can be adjusted by changing the ratio of calcium sulfoaluminate binder, gypsum, silicate cement, carbonate and boric acid.
[0028] Silica fume can fill the pores between material particles and form a gel with hydration products, which can significantly improve the compression resistance, flexural resistance, impermeability, corrosion resistance, impact resistance and wear resistance. Quartz sand has the characteristics of high hardness and high wear resistance, which can increase the strength and stability of maintenance and rescue materials. Redispersible latex powder (using commonly used latex powder in this field, not limited here) is used to improve the interfacial bonding strength and reduce the elastic modulus. The dye is a commonly used dye in this field, which is used to color the maintenance and rescue materials to reduce the color difference between the maintenance and rescue materials after repair and the original bridge deck or road pavement layer, and improve the aesthetics. The use of polycarboxylic acid high-performance water reducer can effectively disperse cement particles and has a good steric hindrance effect, which makes the repair material have the best construction performance. Hydroxypropyl methylcellulose can improve the later strength and toughness of the maintenance and rescue materials. The surfactant uses P803 defoamer to eliminate bubbles generated during the preparation of mortar. The fiber provides anti-cracking performance. The addition of expansion agent and resin can synergistically resist the shrinkage of cement and reduce the risk of cracking. Adding graphene helps improve strength, toughness, durability and frost resistance.
[0029] Furthermore, the maintenance and rescue materials include the following raw materials in proportion by weight: 25-30 parts of calcium sulfoaluminate binder, 5-10 parts of gypsum, 2-4 parts of Portland cement, 1-5 parts of silica fume, 54-57 parts of quartz sand, 0.5-1 parts of fiber, 1.5-2 parts of redispersible latex powder, 0.4-0.6 parts of colorant, 0.1-1 parts of boric acid, 0.05-0.5 parts of carbonate, 0.5-1 parts of polycarboxylic acid high-performance water reducer, 0.1-0.5 parts of hydroxypropyl methylcellulose, 0.2-0.3 parts of surfactant, 0.1-0.2 parts of resin, 0.05-0.06 parts of expansion agent, and 0.02-0.03 parts of graphene.
[0030] Furthermore, the strength grade of the calcium sulfoaluminate binder is 72.5, and the strength grade of the silicate cement is 42.5.
[0031] Furthermore, the quartz sand comprises, by weight: 35-45 parts of quartz sand with a particle size of 10-20 mesh, 7-15 parts of quartz sand with a particle size of 40-70 mesh, and 8-15 parts of quartz sand with a particle size of 70-140 mesh.
[0032] Quartz sand has high hardness, strong toughness and good wear resistance. Adding it to the material can improve the strength and hardness of the curing and rescue materials. However, quartz sand of different particle sizes has different effects on curing and rescue materials. As the particle size of quartz sand increases, the compressive strength of curing and rescue materials also increases. However, the gaps between large-particle quartz sand are large, which will have an adverse effect on the dispersion of fibers in the curing and rescue materials. Although small-particle quartz sand can also improve the strength and hardness of curing and rescue materials, the effect is not as obvious as that of large-particle quartz sand. At the same time, when too much small-particle quartz sand is added, the durability of curing and rescue materials will be reduced. Therefore, quartz sand of different particle sizes is mixed, with large-particle quartz sand as the main material and small-particle quartz sand as the auxiliary material, so that small-particle quartz sand can fill more gaps between large-particle quartz sand, thereby improving the strength and hardness of curing and rescue materials.
[0033] Furthermore, the fibers are mixed by polyacrylonitrile fibers and nanocarbon fibers in a mass ratio of (1-2):1.
[0034] Polyacrylonitrile fiber can provide anti-cracking performance for maintenance and rescue materials, but the size of polyacrylonitrile fiber is large and it is scattered inside the maintenance and rescue materials. Although it can play a bridging role and improve the integrity of the maintenance and rescue materials, it cannot fill the pore structure inside the maintenance and rescue materials. It has certain limitations when used alone. Therefore, nano-carbon fiber can be added to the maintenance and rescue materials at the same time as the polyacrylonitrile fiber is added. Nano-carbon fiber has the characteristics of small size and large specific surface area. When it is added to the maintenance and rescue materials, it can fill the pores inside the maintenance and rescue materials well, making the maintenance and rescue materials more compact, and then effectively resist the invasion of external media to improve the durability of the maintenance and rescue materials. Nano-carbon fiber also has the characteristics of high aspect ratio and high toughness. When it is added to the maintenance and rescue materials, it can play the bridging role of the fiber, penetrate the pores inside the maintenance and rescue materials, make the internal connection of the maintenance and rescue materials more tightly, and then enhance the bridging role played by the polyacrylonitrile fiber, thereby improving the mechanical properties of the maintenance and rescue materials.
[0035] The doping amount of nanocarbon fiber should be less than that of polyacrylonitrile fiber, and it is used as an auxiliary agent for polyacrylonitrile fiber. This is because when the doping amount of nanocarbon fiber is too much, the van der Fas force between the surface molecules of the nanocarbon fiber increases, making the nanocarbon fibers attract each other and difficult to disperse, which causes the nanocarbon fibers to clump inside the maintenance and rescue materials, causing large or even through cracks inside the maintenance and rescue materials, which will reduce the overall density of the maintenance and rescue materials and reduce the effect of the nanocarbon fiber.
[0036] Furthermore, the expansion agent is a mixture of a calcium oxide expansion agent and a magnesium oxide expansion agent in a mass ratio of (1-1.5):1.
[0037] The rapid reaction between calcium oxide expansion agent and water can compensate for early shrinkage, and magnesium oxide expansion agent is suitable for reducing late shrinkage. The combination of the two can effectively compensate for the shrinkage of cement mortar.
[0038] Furthermore, the carbonate is lithium carbonate or sodium carbonate, and the mass ratio of the carbonate to the graphene is 6:(0.5-5).
[0039] When the temperature difference between day and night is too large, the temperature difference between the inside and the surface of the maintenance and rescue material components will be too large, resulting in cracks, which will affect the service life of the maintenance and rescue materials. In addition, when the temperature is low, the maintenance and rescue materials cannot meet the design strength requirements and are prone to quality problems. Therefore, graphene is added to the maintenance and rescue materials to improve the frost resistance and durability of the maintenance and rescue materials. The doping of graphene will promote the sufficiency and completeness of the hydration reaction, increase the amount of Ca(OH)2 gel, and graphene can be filled in the "grid structure" of the maintenance and rescue material, so that the hydration product gel and the material are more densely combined. The addition of carbonate will react with the Ca(OH)2 produced by the hydration reaction to generate CaCO3, which consumes Ca(OH)2 during the reaction and reduces Ca 2+ The ion concentration of carbonate can react with OH - Combined with the formation of a strong base, it further promotes the continuous hydration of the material. At the same time, the Ca(OH)2 gel is converted into CaCO3, which can fill the pores and gaps in the hardened cement body, optimize the microstructure of the hardened cement body, and improve the density. Through the synergistic effect of the two, not only can the rate of hydration reaction be increased, the early strength of cement can be increased, but also the overall mechanical properties of the material, especially the compressive resistance and corrosion resistance, can be improved.
[0040] Preferably, the graphene is graphene oxide. The carbon chain structure of graphene oxide has numerous oxygen-containing functional groups, such as hydroxyl, ether and epoxy groups. These oxygen-containing functional groups can enable graphene to better combine with cement-based materials. Due to its own hydrophilicity, graphene oxide can absorb excess moisture in the curing and rescue materials, thereby increasing the compactness between the matrices and increasing the compressive strength of the curing and rescue materials.
[0041] When adding carbonate and graphene to the material, the ratio between the two should be strictly controlled. Graphene has a large specific surface area. When the doping amount is too high, it is easy to agglomerate in the material, which leads to uneven distribution of graphene and local pores, resulting in a decrease in the mechanical properties of the material. The hydration reaction is an exothermic reaction. When the carbonate dosage is large, the hydration reaction is too fast. The excessively high hydration temperature causes stress inside and outside the cement, thereby reducing the overall performance of the material. Therefore, the ratio between carbonate and graphene is controlled to maximize the synergistic effect of the two.
[0042] Furthermore, the resin is a water-absorbing resin, and the mass ratio of the resin to the expansion agent is 1:(0.05-1.2).
[0043] When the shrinkage of the curing and rescue materials is regulated by a combination of an expansion agent and a water-absorbing resin (commonly used water-absorbing resins in the art are used, which are not limited here), the expansion agent can increase the early water consumption and fill the micropores, while the water-absorbing resin has the function of pre-absorbing water and residual pores. Therefore, when the expansion agent and the water-absorbing resin are used in combination, a synergistic effect is produced in the early shrinkage reduction, crack control and mechanical strength development of the curing and rescue materials.
[0044] Preferably, the maintenance and rescue material also contains an anti-self-shrinkage agent, the amount of the anti-self-shrinkage agent is 0.1wt%-0.2wt% of the total weight of the maintenance and rescue material, and the anti-self-shrinkage agent is a mixture of cationic starch, kaolin and sodium carboxymethyl dextran, wherein the mass ratio of cationic starch, kaolin and sodium carboxymethyl dextran is (4-5): (0.5-1): (1-1.5).
[0045] The Si-OH on the surface of kaolin has certain activity and can be linked with the molecular chain of sodium carboxymethyl dextran. At the same time, kaolin can also form hydrogen bonds with hydrophilic groups such as -NH2 and -OH in cationic starch, thereby forming a network microporous structure with kaolin particles as cross-linking points, thereby increasing water absorption. In addition, the hydrophilic groups such as -COO- and -OH on sodium carboxymethyl dextran can form hydrogen bonds with water molecules and promote the absorption of water by the anti-self-shrinkage agent. The synergistic effect of kaolin and sodium carboxymethyl dextran can improve the water absorption performance, so that the water inside the maintenance and rescue materials is more abundant, thereby delaying the shrinkage of the fine pores inside the maintenance and rescue materials, and indirectly delaying the drying shrinkage of the maintenance and rescue materials. However, the amount of kaolin and sodium carboxymethyl dextran should not be too much: when the amount of kaolin is too much, more kaolin particles are physically filled in the network micropores while cross-linking, making the network micropores appear too narrow, thus low water absorption. In addition, the water absorption of kaolin molecules is poor, and excessive use also reduces the water absorption of the anti-self-shrinking agent. The viscosity of sodium carboxymethyl dextran solution is extremely high. When too much sodium carboxymethyl dextran is added, the viscosity of the reaction system usually increases sharply, restricting the movement of the molecular chain and thus reducing the water absorption rate.
[0046] The anti-self-shrinkage agent composed of cationic starch, kaolin, and sodium carboxymethyl dextran can not only absorb and release water by itself, but also strengthen the performance of the water-absorbing resin through synergistic action, so that the water-absorbing resin can absorb a large amount of water in a short time. After absorbing water, the water-absorbing resin undergoes significant volume swelling, thereby forming a hydrogel, which quickly blocks the cracks in the maintenance and rescue materials. With the consumption of water in the maintenance and rescue materials, the suction force formed by the gradually increasing capillary negative pressure in the cement-based materials, and the increasing osmotic pressure of the porous solution as the cement hydration proceeds, the water in the water-absorbing resin is gradually released, thereby reducing the self-drying stress in the hardened slurry, avoiding the situation in some dry areas where the self-drying stress is too large during the self-shrinkage phenomenon, and then cracks occur, thereby improving the compressive resistance and later strength of the maintenance and rescue materials. At the same time, the expansion product when an appropriate amount of expansion agent reacts with the water in the maintenance and rescue materials can fill the residual pores after the water release of the super absorbent resin, thereby having a favorable effect on the compressive strength of the maintenance and rescue materials.
[0047] Furthermore, the preparation steps of the maintenance and rescue materials are as follows:
[0048] Weigh the following raw materials by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.1 parts of expansion agent, and 0.01-0.05 parts of graphene;
[0049] Calcium sulphoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A;
[0050] The expansion agent and the resin are mixed evenly in a dry powder state to obtain dry material B;
[0051] Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, and 4wt%-6wt% of water is added thereto and stirred to mix uniformly to obtain slurry C;
[0052] Mix dry material A, slurry C, and 70% of a surfactant, add 6wt%-8wt% of water thereto, and stir and mix to obtain slurry D;
[0053] The dry material B, the slurry D and the dye are mixed, 1wt%-3wt% of water is added thereto, and the mixture is stirred and mixed evenly to obtain the curing and rescue material.
[0054] Preferably, the steps for preparing the maintenance and rescue materials are as follows:
[0055] Weigh the following raw materials by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.08 parts of expansion agent, 0.01-0.05 parts of graphene, and 0.08-0.26 parts of anti-self-shrinkage agent;
[0056] Calcium sulphoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A;
[0057] The expansion agent, resin and anti-self-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1;
[0058] Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, and 4wt%-6wt% of water is added thereto and stirred to mix uniformly to obtain slurry C;
[0059] Mix dry material A, slurry C, and 70% of a surfactant, add 6wt%-8wt% of water thereto, and stir and mix well to obtain slurry D;
[0060] The dry material B1, the slurry D and the dye are mixed, 1wt%-3wt% of water is added thereto, and the mixture is stirred and mixed evenly to obtain a curing and rescue material.
[0061] The present invention is further described in detail below in conjunction with specific embodiments.
[0062] Example 1
[0063] Construction environment: temperature: 20℃, humidity: ≥50%;
[0064] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0065] A cement-based bridge deck maintenance and rescue material comprises the following raw materials in parts by weight (g): 35 parts of calcium sulfoaluminate binder, 5 parts of gypsum, 2 parts of silicate cement, 5 parts of silica fume, 57 parts of quartz sand (including 41 parts of 10-20 mesh, 7 parts of 20-40 mesh, and 9 parts of 70-140 mesh), 0.5 parts of fiber (including polyacrylonitrile fiber and carbon fiber in a ratio of 2:1), 2 parts of redispersible latex powder, 0.7 parts of dye, 0.1 parts of boric acid, 0.3 parts of lithium carbonate, 0.7 parts of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of hydroxypropyl methylcellulose, 0.5 parts of surfactant, 0.2 parts of resin, 0.06 parts of expansion agent (including calcium oxide expansion agent and magnesium oxide expansion agent in a ratio of 1:1), 0.02 parts of graphene, and 0.08 parts of anti-self-shrinkage agent (including cationic starch, kaolin, and sodium carboxymethyl polyglucose in a ratio of 4:0.5:1).
[0066] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0067] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0068] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0069] 3) Fiber, hydroxypropyl methylcellulose, boric acid, lithium carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 4 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0070] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 6 wt% of water is added thereto and stirred to obtain slurry D.
[0071] 5) Mix the dry material B1, slurry D and dye, add 1wt% of water and stir to mix evenly to obtain the curing and rescue material. The curing and rescue material is fully mixed, poured and smoothed.
[0072] Example 2
[0073] Construction environment: temperature: 20℃, humidity: ≥50%;
[0074] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0075] A cement-based bridge deck maintenance and rescue material comprises the following raw materials in parts by weight (g): 32 parts of calcium sulfoaluminate binder, 6 parts of gypsum, 2 parts of silicate cement, 4 parts of silica fume, 56 parts of quartz sand (including 40 parts of 10-20 mesh, 8 parts of 20-40 mesh, and 8 parts of 70-140 mesh), 0.6 parts of fiber (including polyacrylonitrile fiber and carbon fiber in a ratio of 1:1), 1.5 parts of redispersible latex powder, 0.6 parts of dye, 0.2 parts of boric acid, 0.1 parts of sodium carbonate, 1.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.1 parts of hydroxypropyl methylcellulose, 0.2 parts of surfactant, 0.1 parts of resin, 0.1 parts of expansion agent (including calcium oxide expansion agent and magnesium oxide expansion agent in a ratio of 1:1), 0.03 parts of graphene, and 0.26 parts of anti-self-shrinkage agent (including cationic starch, kaolin, and sodium carboxymethyl polyglucose in a ratio of 5:1:5).
[0076] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0077] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0078] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0079] 3) Fiber, hydroxypropyl methylcellulose, boric acid, sodium carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 6 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0080] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 8 wt% of water is added thereto and stirred to obtain slurry D.
[0081] 5) Mix the dry material B1, slurry D and dye, add 3wt% of water and stir to obtain the curing and rescue material. After the curing and rescue material is fully mixed, pouring and smoothing are completed.
[0082] Example 3
[0083] Construction environment: temperature: 20℃, humidity: ≥50%;
[0084] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0085] A cement-based bridge deck maintenance and rescue material, comprising the following raw materials in parts by weight (g): 30 parts of calcium sulfoaluminate binder, 8 parts of gypsum, 3 parts of silicate cement, 4 parts of silica fume, 56 parts of quartz sand (including 37 parts of 10-20 mesh, 11 parts of 20-40 mesh, and 8 parts of 70-140 mesh), 0.8 parts of fiber (including a ratio of polyacrylonitrile fiber to carbon fiber of 1.5:1), 2.2 parts of redispersible latex powder, and 0.5 parts of dye. 0.4 parts, boric acid 0.6 parts, sodium carbonate 0.6 parts, polycarboxylic acid high-efficiency water reducing agent 0.6 parts, hydroxypropyl methylcellulose 0.3 parts, surfactant 0.4 parts, resin 0.3 parts, expander 0.05 parts (the ratio of calcium oxide expander to magnesium oxide expander is 1:1.2), graphene 0.05 parts, anti-self-shrinkage agent 0.2 parts (the ratio of cationic starch, kaolin and sodium carboxymethyl polyglucose is 4.5:0.7:1.2).
[0086] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0087] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0088] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0089] 3) Fiber, hydroxypropyl methylcellulose, boric acid, sodium carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 5 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0090] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 7 wt % of water is added thereto and stirred to obtain slurry D.
[0091] 5) Mix the dry material B1, slurry D and dye, add 2wt% of water and stir to mix evenly to obtain the curing and rescue material. The curing and rescue material is fully mixed, poured and smoothed.
[0092] Example 4
[0093] Construction environment: temperature: 20℃, humidity: ≥50%;
[0094] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0095] A cement-based bridge deck maintenance and rescue material comprises the following raw materials in parts by weight (g): 30 parts of calcium sulfoaluminate binder, 8 parts of gypsum, 3 parts of silicate cement, 2 parts of silica fume, 55 parts of quartz sand (including 38 parts of 10-20 mesh, 9 parts of 20-40 mesh, and 8 parts of 70-140 mesh), 1.1 parts of fiber (including the ratio of polyacrylonitrile fiber to carbon fiber being 1.7:1), 1.5 parts of redispersible latex powder, 0.5 parts of dye, 0.6 parts of boric acid, 0.5 parts of lithium carbonate, 0.8 parts of polycarboxylic acid high-efficiency water reducing agent, 0.4 parts of hydroxypropyl methylcellulose, 0.3 parts of surfactant, 0.1 parts of resin, 0.05 parts of expansion agent (including the ratio of calcium oxide expansion agent to magnesium oxide expansion agent being 1:1), 0.03 parts of graphene, and 0.15 parts of anti-self-shrinkage agent (including the ratio of cationic starch, kaolin, and sodium carboxymethyl polyglucose being 5:0.5:1.5).
[0096] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0097] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0098] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0099] 3) Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 4 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0100] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 8 wt% of water is added thereto and stirred to obtain slurry D.
[0101] 5) Mix the dry material B1, slurry D and dye, add 1wt% of water and stir to mix evenly to obtain the curing and rescue materials. The curing and rescue materials are fully mixed, poured and smoothed.
[0102] Example 5
[0103] Construction environment: temperature: 20℃, humidity: ≥50%;
[0104] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0105] A cement-based bridge deck maintenance and rescue material comprises the following raw materials in parts by weight (g): 27 parts of calcium sulfoaluminate binder, 10 parts of gypsum, 3 parts of silicate cement, 2 parts of silica fume, 54 parts of quartz sand (including 38 parts of 10-20 mesh, 8 parts of 20-40 mesh, and 8 parts of 70-140 mesh), 1 part of fiber (including polyacrylonitrile fiber and carbon fiber in a ratio of 1:1), 1.5 parts of redispersible latex powder, 0.5 parts of dye, 0.8 parts of boric acid, 0.5 parts of lithium carbonate, 1 part of polycarboxylic acid high-efficiency water reducing agent, 0.2 parts of hydroxypropyl methylcellulose, 0.5 parts of surfactant, 0.2 parts of resin, 0.12 parts of expansion agent (including calcium oxide expansion agent and magnesium oxide expansion agent in a ratio of 1.3:1), 0.03 parts of graphene, and 0.2 parts of anti-self-shrinkage agent (including cationic starch, kaolin, and sodium carboxymethyl polyglucose in a ratio of 4:0.5:1).
[0106] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0107] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0108] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0109] 3) Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 6 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0110] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 7 wt % of water is added thereto and stirred to obtain slurry D.
[0111] 5) Mix the dry material B1, slurry D and dye, add 3wt% of water and stir to mix evenly to obtain the curing and rescue material. The curing and rescue material is fully mixed, poured and smoothed.
[0112] Example 6
[0113] Construction environment: temperature: 20℃, humidity: ≥50%;
[0114] Maintenance environment: temperature: 20℃, humidity: ≥90%.
[0115] A cement-based bridge deck maintenance and rescue material is prepared by mixing the following raw materials in parts by weight (g): 25 parts of calcium sulfoaluminate binder, 10 parts of gypsum, 4 parts of silicate cement, 1 part of silica fume, 57 parts of quartz sand (including 36 parts of 10-20 mesh, 10 parts of 20-40 mesh, and 11 parts of 70-140 mesh), 1 part of fiber (including polyacrylonitrile fiber and carbon fiber in a ratio of 2:1), 1.5 parts of redispersible latex powder, 0.3 parts of dye, 1.2 parts of boric acid, 0.1 parts of lithium carbonate, 1 part of polycarboxylic acid high-efficiency water reducing agent, 0.5 parts of hydroxypropyl methylcellulose, 0.3 parts of surfactant, 0.2 parts of resin, 0.1 parts of expansion agent (including calcium oxide expansion agent and magnesium oxide expansion agent in a ratio of 1.5:1), 0.02 parts of graphene, and 0.15 parts of anti-self-shrinkage agent (including cationic starch, kaolin, and sodium carboxymethyl polyglucose in a ratio of 4.5:0.5:1.5).
[0116] A method for preparing a cement-based bridge deck maintenance and rescue material comprises the following steps:
[0117] 1) After weighing, the calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed in a dry powder state to obtain dry material A.
[0118] 2) The expansion agent, resin and anti-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B1.
[0119] 3) Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent graphene, and 30% of a surfactant are mixed, 5 wt % of water is added thereto, and the mixture is stirred and mixed to obtain slurry C.
[0120] 4) Dry material A, slurry C, and 70% of a surfactant are mixed, and 6 wt% of water is added thereto and stirred to obtain slurry D.
[0121] 5) Mix the dry material B1, slurry D and dye, add 3wt% of water and stir to mix evenly to obtain the curing and rescue material. The curing and rescue material is fully mixed, poured and smoothed.
[0122] The performance indicators of the cement-based bridge deck maintenance and rescue materials of Examples 1-6 are shown in Table 1:
[0123] Table 1
[0124] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Initial setting time (min) 33 42 57 67 74 85 Final setting time (min) 41 56 70 82 89 102 1h compressive strength (MPa) 21.5 / / / / / 2h compressive strength (MPa) 33.8 21.8 14.8 6.3 / / 4h compressive strength (MPa) 42.3 35.9 31.7 22.3 16.2 12.7 6h compressive strength (MPa) 46.7 44.3 40.1 36.3 32.9 23.3 1d compressive strength (MPa) 55.4 53.5 51.4 47.2 42.1 38.4 1d bonding strength (MPa) 2.9 2.8 2.7 2.5 2.3 2.2 3d compressive strength (MPa) 60.9 60.7 60.5 60.3 60.6 60.8 28d compressive strength (MPa) 73.0 73.2 73.1 73.3 73.5 73.2 28d bonding strength (MPa) 3.6 3.7 3.6 3.7 3.7 3.8 28d impact resistance 83 84 82 83 82 84
[0125] It can be seen from the data of Examples 1-6 and Table 1 that the initial setting time and final setting time of the cement-based bridge deck maintenance and rescue material provided by the present invention can be adjusted by changing the ratio of calcium sulfoaluminate binder, gypsum, silicate cement, carbonate and boric acid to meet the needs of construction personnel, minimize the impact of the construction period on traffic closure, reduce construction difficulty, and improve work efficiency. At the same time, the components in the cement-based bridge deck maintenance and rescue material work synergistically with each other, improving the adhesion and impact resistance of the repaired maintenance and rescue material to the original bridge deck pavement layer, so that the material has excellent mechanical properties.
[0126] Comparative Example 1
[0127] The difference between Comparative Example 1 and Example 1 is that no anti-self-shrinkage agent is added.
[0128] Comparative Example 2
[0129] The difference between Comparative Example 2 and Example 1 is that the construction environment is: temperature: 30°C, humidity: ≤50%; the maintenance environment is: temperature: 30°C, humidity: ≤50%.
[0130] Comparative Example 3
[0131] The difference between Comparative Example 3 and Example 1 is that no anti-shrinkage agent is added, and the construction environment is: temperature: 30° C., humidity: ≤50%; the maintenance environment is: temperature: 30° C., humidity: ≤50%.
[0132] Comparative Example 4
[0133] The difference between Comparative Example 4 and Example 6 is that no anti-self-shrinkage agent is added.
[0134] Comparative Example 5
[0135] The difference between Comparative Example 5 and Example 6 is that the construction environment is: temperature: 30°C, humidity: ≤50%; the maintenance environment is: temperature: 30°C, humidity: ≤50%.
[0136] Comparative Example 6
[0137] The difference between Comparative Example 6 and Example 6 is that no anti-shrinkage agent is added, and the construction environment is: temperature: 30°C, humidity: ≤50%; the maintenance environment is: temperature: 30°C, humidity: ≤50%.
[0138] The performance indicators of cement-based bridge deck maintenance and rescue materials of comparative examples 1-6 are shown in Table 2:
[0139] Table 2:
[0140] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Initial setting time (min) 32 32 29 85 85 79 Final setting time (min) 43 41 37 103 101 97 1h compressive strength (MPa) 21.3 21.6 21.7 / / / 2h compressive strength (MPa) 33.6 34.0 34.1 / / / 4h compressive strength (MPa) 42.1 42.4 42.4 12.9 12.8 13.1 6h compressive strength (MPa) 46.6 47.0 47.1 23.6 23.4 23.9 1d compressive strength (MPa) 53.9 55.6 50.4 37.3 38.4 35.6 1d bonding strength (MPa) 2.7 2.7 2.5 2.3 2.2 2.3 3d compressive strength (MPa) 59.5 61.3 55.6 59.9 61.0 58.5 28d compressive strength (MPa) 70.6 73.2 67.9 68.9 73.5 65.9 28d bonding strength (MPa) 3.3 3.8 3.0 3.2 3.8 2.8 28d impact resistance 79 84 76 78 85 73
[0141] It can be seen from the data of Comparative Examples 1 and 4 that, regardless of the length of the solidification time, the anti-self-shrinkage agent will slightly improve the compressive properties of the material in the early stage of solidification, that is, the compressive strength of 1h-1d, and will greatly improve its later compressive properties, that is, the compressive strength after 3d. It can be seen from Comparative Examples 2 and 5 that under the condition of adding anti-self-shrinkage agents, the maintenance and rescue materials can still maintain high compressive strength, adhesion and impact resistance in a high-temperature dry environment. When comparative examples 4 and 6 are in a high-temperature dry environment without the addition of anti-self-shrinkage agents, their initial strength is improved. This is because the high-temperature dry environment accelerates the volatilization of moisture in the material; while their later compressive strength is significantly lower than that of the material with the addition of anti-self-shrinkage agents. This is because the moisture evaporates too quickly, and the self-drying stress is too large during the self-shrinkage phenomenon, resulting in cracks inside the material.
[0142] Comparative Example 7
[0143] The only difference between Comparative Example 7 and Example 2 is that the added fiber is a single polypropylene fiber, and the amount used is the same as the total amount of the fiber in Example 2.
[0144] Comparative Example 8
[0145] The only difference between Comparative Example 8 and Example 2 is that the added fiber is a single nano-carbon fiber, and the amount used is the same as the total amount of the fiber in Example 2.
[0146] Comparative Example 9
[0147] The only difference between Comparative Example 9 and Example 2 is that the added fiber is a mixture of polypropylene fiber and nano-carbon fiber, but the ratio of polypropylene fiber to nano-carbon fiber is 5:1.
[0148] The performance indicators of cement-based bridge deck maintenance and rescue materials of Comparative Examples 7-9 are shown in Table 3:
[0149] Table 3
[0150] Comparative Example 7 Comparative Example 8 Comparative Example 9 Initial setting time (min) 42 41 42 Final setting time (min) 56 44 55 1h compressive strength (MPa) / / / 2h compressive strength (MPa) 21.1 21.5 21.3 4h compressive strength (MPa) 31.9 32.3 32.1 6h compressive strength (MPa) 41.2 40.3 42.4 1d compressive strength (MPa) 47.1 49.1 50.3 1d bonding strength (MPa) 2.5 2.4 2.5 3d compressive strength (MPa) 56.5 57.9 58.5 28d compressive strength (MPa) 67.6 68.4 70.0 28d bonding strength (MPa) 3.2 3.3 3.4 28d impact resistance 74 78 80
[0151] It can be seen from the data of Comparative Examples 7, 8 and 9 that when polyacrylonitrile fiber is used alone or nano-carbon fiber is used alone, the effect is far less good than when the two act in synergy, and the ratio between the two should also be selected reasonably. In Comparative Example 9, the ratio of polyacrylonitrile fiber to nano-carbon fiber is 5:1, which can be found to be not as good as the effect produced by using polypropylene fiber and nano-carbon fiber in a ratio of 1:1 in Example 2. This is because the content of polyacrylonitrile fiber is too high, which reduces the effect of nano-carbon fiber on reinforcing the bridging effect between polyacrylonitrile fibers. Therefore, when the two are used at the same time and the ratio is reasonable, that is, the ratio of polypropylene fiber to nano-carbon fiber is (1-2):1, the fiber gain to the material can reach the maximum value.
[0152] Comparative Example 10
[0153] The only difference between Comparative Example 10 and Example 5 is that the ratio of graphene to lithium carbonate is 20:1.
[0154] Comparative Example 11
[0155] The only difference between Comparative Example 11 and Example 5 is that the ratio of graphene to lithium carbonate is 1:20.
[0156] Comparative Example 12
[0157] The only difference between Comparative Example 12 and Example 5 is that the construction environment is: temperature: 2°C, humidity: ≥20%; the maintenance environment is: temperature: 2°C, humidity: ≥50%.
[0158] The performance indicators of cement-based bridge deck maintenance and rescue materials of comparative examples 10-12 are shown in Table 4:
[0159] Table 4
[0160] Comparative Example 10 Comparative Example 11 Comparative Example 12 Initial setting time (min) 75 70 75 Final setting time (min) 90 85 91 1h compressive strength (MPa) / / / 2h compressive strength (MPa) / / / 4h compressive strength (MPa) 15.9 16.1 16.3 6h compressive strength (MPa) 32.2 32.4 32.8 1d compressive strength (MPa) 40.6 40.7 42.0 1d bonding strength (MPa) 2.0 2.1 2.2 3d compressive strength (MPa) 58.6 57.6 60.3 28d compressive strength (MPa) 70.9 71.8 73.3 28d bonding strength (MPa) 3.4 3.3 3.6 28d impact resistance 77 78 81
[0161] It can be seen from Comparative Example 10 that when the doping amount of graphene is too large, it is easy to agglomerate in the material, which leads to uneven distribution of graphene, local pores, and decreased mechanical properties of the material. It can be seen from Comparative Example 11 that when the doping amount of lithium carbonate is too large, not only the mechanical properties of the material are reduced, but also the setting time of the material is shortened. This is because the hydration reaction is an exothermic reaction. When the carbonate dosage is large, the hydration reaction is too fast, which shortens the setting time. At the same time, the excessively high hydration temperature causes stress inside and outside the cement, thereby reducing the overall performance of the material. Therefore, the ratio between carbonate and graphene is controlled so that the synergistic effect of the two can be maximized. It can be seen from Comparative Example 12 that carbonate and graphene can maintain good mechanical properties at a suitable ratio even if the material is in a relatively low temperature environment.
[0162] The repair construction time of the present invention meets the requirements of "Technical Specification for Maintenance of Highway Cement Concrete Pavement DB61 / T 1586-2022".
[0163] The compressive strength test method in the present invention complies with the requirements of "Test Method for Strength of Cement Mortar (ISO Method) GB / T 17671-2021".
[0164] The bonding strength in the present invention complies with the requirements of "Technical Specification for Safety Appraisal of Engineering Structure Reinforcement Materials GB 50728-2011".
[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cement-based bridge deck maintenance and rescue material, characterized in that: The maintenance and rescue material comprises the following raw materials in proportion by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducing agent, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.1 parts of expansion agent, and 0.01-0.05 parts of graphene; The fiber is formed by mixing polyacrylonitrile fiber and nano-carbon fiber in a mass ratio of (1-2):1; the carbonate is lithium carbonate or sodium carbonate, and the resin is a water-absorbing resin; The maintenance and rescue material also contains an anti-self-shrinkage agent, the amount of which accounts for 0.1wt%-0.2wt% of the total weight of the maintenance and rescue material. The anti-self-shrinkage agent is a mixture of cationic starch, kaolin and sodium carboxymethyl dextran, wherein the mass ratio of cationic starch, kaolin and sodium carboxymethyl dextran is (4-5): (0.5-1): (1-1.5).
2. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The maintenance and rescue material includes the following raw materials in proportion by weight: 25-30 parts of calcium sulfoaluminate binder, 5-10 parts of gypsum, 2-4 parts of silicate cement, 1-5 parts of silica fume, 54-57 parts of quartz sand, 0.5-1 parts of fiber, 1.5-2 parts of redispersible latex powder, 0.4-0.6 parts of coloring agent, 0.1-1 parts of boric acid, 0.05-0.5 parts of carbonate, 0.5-1 parts of polycarboxylic acid high-performance water reducing agent, 0.1-0.5 parts of hydroxypropyl methylcellulose, 0.2-0.3 parts of surfactant, 0.1-0.2 parts of resin, 0.05-0.06 parts of expansion agent, and 0.02-0.03 parts of graphene.
3. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The strength grade of the calcium sulfoaluminate binder is 72.5, and the strength grade of the silicate cement is 42.
5.
4. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The quartz sand comprises, by weight, 35-45 parts of quartz sand with a particle size of 10-20 meshes, 7-15 parts of quartz sand with a particle size of 40-70 meshes, and 8-15 parts of quartz sand with a particle size of 70-140 meshes.
5. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The expansion agent is prepared by mixing a calcium oxide expansion agent and a magnesium oxide expansion agent in a mass ratio of (1-1.5):
1.
6. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The mass ratio of the carbonate to the graphene is 6:(0.5-5).
7. The cement-based bridge deck maintenance and rescue material according to claim 1, characterized in that: The mass ratio of the resin to the expansion agent is 1:(0.05-1.2).
8. A method for preparing the cement-based bridge deck maintenance and rescue material according to any one of claims 1 to 7, characterized in that: The preparation steps of the maintenance and rescue material are as follows: The following raw materials are weighed in parts by weight: 20-35 parts of calcium sulfoaluminate binder, 3-13 parts of gypsum, 1.5-6 parts of silicate cement, 0.8-6 parts of silica fume, 50-60 parts of quartz sand, 0.4-1.3 parts of fiber, 1-2.5 parts of redispersible latex powder, 0.3-0.8 parts of dye, 0.05-1.2 parts of boric acid, 0.03-0.6 parts of carbonate, 0.2-2 parts of polycarboxylic acid high-performance water reducer, 0.08-0.8 parts of hydroxypropyl methylcellulose, 0.1-0.5 parts of surfactant, 0.05-0.3 parts of resin, 0.03-0.08 parts of expansion agent, 0.01-0.05 parts of graphene and the anti-self-shrinkage agent, wherein the amount of the anti-self-shrinkage agent accounts for 0.1wt%-0.2wt% of the total weight of the maintenance and rescue materials; Calcium sulfoaluminate binder, gypsum, silicate cement, silica fume, quartz sand and redispersible latex powder are mixed uniformly in a dry powder state to obtain dry material A; The expansion agent, resin and anti-self-shrinkage agent are mixed evenly in a dry powder state to obtain dry material B; Fiber, hydroxypropyl methylcellulose, boric acid, carbonate, polycarboxylic acid high-performance water-reducing agent, graphene, and 30% of a surfactant are mixed, and 4wt%-6wt% of water is added thereto and stirred to mix evenly to obtain slurry C; Mix dry material A, slurry C, and 70% of a surfactant, add 6wt%-8wt% of water thereto, and stir and mix well to obtain slurry D; The dry material B, the slurry D and the dye are mixed, and 1wt%-3wt% of water is added thereto and stirred to mix evenly to obtain the curing and rescue material.
Citation Information
Patent Citations
Cement grouting material
CN104844122A
Bridge expansion joint fast reparation material
CN105523745A